(Nie)zgodnie z przekonaniami ojca, (nie)zgodnie z Biblią, czyli o intertekstualnym świecie odniesień biblijnych w powieści Franz i François Françoisa Weyergansa - Jarosz, Adam (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The Bible, called by Northrop Frye “the great code”, is an inexhaustible collection of great symbolic images and a source of ethical norms. This – what one might call the pedagogic or educational aspect of the Bible – is powerfully present in the autobiographical novel by François Weyergans entitled Franz and François. Weyergans’s novel is not just a study of a difficult relationship between father and son, but also an excuse for creating a unique narrative space in which the main protagonist, François, initiates a dialogue with the Bible (perceived through a system of intertextual references), and with various interpretations thereof, put forward by his father, Franz, a Catholic novelist. Taking into account the highly polemical bent of the dialogue, the aim of the present paper is not a systematic presentation of all the biblical references and allusions detected in the novel, but, rather, an attempt to present a few existentially fraught situations from the life of François. In these contexts the Bible and its interpretation propounded by the father become an important (although by no means blindly accepted) reference point in the process of the formation of the boy’s personality. Against the intentions of the father, François gradually moves away from biblical values. Does this process amount to a failure of the Bible itself, or just of the father’s educational undertakings? However it might be, the novels certainly constitutes a powerful warning against the rash, exalted biblical exegesis of the writer-father, which leads inexorably to emotional troubles in the boy and to a discrediting of biblical values in his eyes.